Consumer Behavior of Panic Buying Towards the Spread of the Sars-Cov-2 Virus in Ambon City - Arizal Hamizar (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2023)
This study aims to determine how the risk perception factor and the risk attitude factor change the Intentional Behavior and Actual Behavior of consumers so that they do panic buying during the COVID-19 pandemic in Indonesia, especially in Maluku. The approach used is qualitative research with the type of case study. Data was collected by interview and observation, with data analysis techniques of data reduction, data display, and verification. S-O-R and TPB are used to see consumer panic buying behavior during a pandemic. The results of the study show that there are stimuli that influence behavior, including: Stimulus of familiarity, controllability, and information/risk exposure. These stimuli form Risk Perception and then become Risk Attitude.